Implementing European priorities in VET: Germany - Huismann, Adrienne [Verfasser]; Hippach-Schneider, Ute [Verfasser] (Bundesinstitut für Berufsbildung, 2024)
„This VET policy brief produced by Cedefop presents a snapshot of vocational education and training policy developments in Germany between 2020 and the beginning of 2023. It presents the context and the challenges the country faces, a selection of the latest VET-related statistics, as well as the national priorities until 2030 identified in Germany’s national implementation plan. This VET policy brief provides information from Cedefop monitoring and analysis on the implementation of the Council Recommendation on VET and Osnabrück Declaration. It offers stakeholders a regular source of information on VET policy developments that could be used for future policy making.“ (editor; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; 370; Berufsbildung; Berufsbildungspolitik; Quantitative Angaben; 2020-2023